RetinalNet-500: a newly developed CNN model for eye disease detection - Toki, Sadikul Alim; Rahman, Sohanoor; Fahim, SM Mohtasim Billah; Mostakim, Abdullah Al (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.